Alternatives for the serological assessment of foot-and-mouth disease vaccine immunity in buffaloes (Bubalus bubalis) - Sala, Juan Manuel; Trotta, Myrian Vanesa; Mansilla, Florencia Celeste; Perez Filgueira, Daniel Mariano; Caspe, Sergio Gaston; Capozzo, Alejandra (2018)
Buffaloes are compulsory vaccinated against foot-and-mouth disease virus (FMDV) in many countries as part of the official control programmes. Serological testing aimed to indirectly assess herd immunity is currently performed using the same Enzyme-linked immunosorbent assays (ELISAs) applied for bovine sera, assuming an agreement between the ELISA’s diagnostic results and those obtained using the virus neutralization test (VNT). Here we evaluated the accuracy of different ELISA tests to assess vaccine-induced antibodies against FMDV in buffalo’s sera classified according to their VNT titres. Currently used liquid-phase blocking ELISA yielded very low specificity, producing high titres for many samples with low VNT titres. To increase specificity, we developed an indirect ELISA using purified 140S viral particles and an avidity single-dilution ELISA, which includes a urea washing step after the incubation of the diluted serum sample, to detach weak binders. Combining these two high-throughput single-dilution tests, an excellent concordance with VNT was achieved. This is the first study analysing the diagnostic agreement of traditional and novel serological tests with VNT for the indirect assessment of antibodies against FMDV capsid proteins in buffalo serum samples.